The Use of Youtube for Learning English: Exploring Technology-Based Approach - Miftahulfadlik Dabamona; Andarifa Yunus (Universitas Negeri Makassar, 2022)
Abstract. This research shed light on how students’ use YouTube for learning English and also try to explore their technology-based approach. This research conducted at State Islamic Institute of Sorong which involved six participants from English Education Program. The researcher used purposeful sampling to select the participants who actively engaged learning with YouTube. To collect data and information the researcher used descriptive qualitative approach. To validate data the triangulation technique was used using observation, interview, and document instruments. The researcher also used data code for analyzing data. The results showed that YouTube can be use as tool for learning English to support students in learning English independently in informal situation as well as giving a wider opportunity to improve their English skills. The study also found that YouTube can be used as educational technology which supports students’ technology-based approach by facilitating learning that are more independent along with give an experience to learn more fun, interesting, motivating, and learning more effectively and efficiently. Keywords: YouTube, Learning English, Technology-based Approach